A Bibliometric Analysis on Indonesia Education Tourism - Purba, Sopar Parulian; Fatimah, Dinda Putri; Kusumaningrum, Anisa Putri; Pradini, Gagih; Agustiani, Fitri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Educational tourism research developed within a few years. However, there are still few who provide a global picture of the concept. The purpose of this study is to identify trends in educational tourism as well as other scientific products over time, such as sources, authors, and types of documents. Bibliometric analysis was used to analyze a sample of 183 articles from Google Scholar published in 2023 Educational tourism is the main keyword used in article titles, abstracts, and keywords to obtain metadata retrieved from the Google Scholar bibliographic database, on Thursday, October 19, 2023. The tools used in bibliometric analysis are Microsoft Excel which is used to perform frequency analysis, VoS viewer for data visualization, and Harzing's Publish or Perish, which is used for citation and analysis metrics. This study's results show that most related articles are published in scientific journals, compared to others. Related articles published in scientific journals have obtained the highest citations compared to others. Articles are also found in English. Based on network visualization the most dominant term (often appears) is "education tourism". When viewed from the Overlay Visualization, the topic of "education tourism" shows the latest trends in research related to "rural communities